(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Demarcating corona virus strategy in Jammu and Kashmir is most vital approach that can reduce the continuous rise of COVID-19 confirmed cases. In Jammu and Kashmir and in the world, the proper vaccination of COVID-19 is lacking behind. Jammu and Kashmir is a union territory with a reduced amount of resourceful medical background. So this study aimed to show the influence of most of the strategies in Jammu and Kashmir to curb the COVID-19 pandemic, by using the method of ‘personal interview’. By using this technique in this study, can support most of the decision makers, researchers, government of Jammu and Kashmir to grasp the status quo and get most of the awareness about spreading of COVID-19 pandemic and to curb this pandemic for future prevention. This approach followed by the people in Jammu and Kashmir attain results in more recoveries in the COVID-19 cases like imposing complete curfew in those areas where there where high rise in cases. This study also reveals that the government should take some initiatives to make some policies, rules and regulations, strategies to overcome the stress and depression that is caused among the population of Jammu and Kashmir due to this COVID-19 pandemic. This study also revealed that government should make some arrangements like constructing separate hospitals, COVID-19 test centres, COVID care centres to combat this pandemic.